Impacts of the Use of Facebook on Foreign Language Learning among Malagasy High School Students in Analamanga - Andrianjary Myriam; Rahanetra Dina; Rakotoson Olivia; Fidelio Arnold; Ratiarimananjatovo Narindra; Ratsimandisa Haritiana Zo; Rakotomalala Nivomboahangy Razanamiarisoa; Koto-te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina Baholy (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2024)
In an increasingly interconnected world, digital tools are rapidly revolutionizing the methods of teaching and learning foreign languages. In Madagascar, a nation undergoing continuous development, the use of the social platform Facebook is emerging as a powerful catalyst for practicing foreign languages such as French and English for secondary school students. In the digital era, where geographical boundaries are losing significance and learning opportunities are endless, the question emerges: "How can the use of Facebook benefit the learning of foreign languages in Malagasy secondary schools?" Despite the prominent status of these international languages and their importance for development, many challenges remain in making them accessible to all. Even after six years of studying English and starting French from their first year of school, secondary school students still face obstacles in learning and practicing these languages, particularly in vocabulary, pronunciation, grammar, oral expression, and motivation. In this context, a study conducted during the 2023-2024 school year over a two-month period surveyed 78 students in the 10th, 11th, and 12th grades at FJKM Rasalama Manjakaray College, Lycée Privé Fanovozantsoa Ivato, FJKM Fahasoavana Androndra College, FJKM Andriamanarefo High School, and Lycée Privé Rakoto Benjamin Jean Ambohidroa in Antananarivo on their use of Facebook to practice French and English in their daily lives. Simultaneously, 11 French and English teachers were also interviewed about the impact of this social network on their teaching practices and the learning of these foreign languages. The results revealed that many students use this platform as a valuable tool for learning and practicing foreign languages, particularly for acquiring new vocabulary and improving pronunciation, as well as in commenting on posts in French and English. Similarly, the teachers interviewed reported concrete benefits, such as increased student motivation through listening to and watching videos selected or recommended by native teachers or by the students themselves, as well as their active participation in French and English-speaking groups. Despite these advantages, spelling and/or grammar mistakes are observed on social networks, which may undermine their reliability as educational models. Therefore, it is important to find reliable and professional pages and groups, such as those recommended by teachers. The aim of this study is to highlight the importance and effectiveness of social networks as a platform for learning foreign languages in Malagasy schools. This underscores the vital importance of new technologies as innovative tools in the field of education in Madagascar, offering young people unprecedented access to educational resources.